Skor TriAge+ sebagai Alat Diagnostik Klinis Awal Vertigo Sentral pada Stroke Serebelum – Laporan Kasus: Laporan Kasus - Vidyarni, Kurnia Elka; Irawati, Dyah (PT Kalbe Farma Tbk., 2026)
Introduction: Vertigo is a common complaint in the emergency department (ED); however, differentiating central from peripheral vertigo remains challenging. More than 4.4 million patients present to the emergency department annually with dizziness or vertigo, and approximately 5% are diagnosed with stroke. Early identification of central vertigo is crucial to prevent adverse neurological outcomes. Case: A 63-year-old male presented with severe swaying dizziness accompanied by nausea, rendering him unable to walk. The TriAge+ score was 9, indicating high risk for stroke. On the fourth day of hospitalization, the patient developed weakness in the right extremities and impaired sensory function in the bilateral cranial nerve V distribution. Non-contrast head CT revealed a subacute ischemic cerebral infarction affecting the pons, right corona radiata, and bilateral basal ganglia, with signs of brain atrophy. The patient was diagnosed with central vertigo due to cerebellar infarct stroke. Discussion: The TriAge+ score demonstrates high sensitivity for detecting central vertigo in the ED. In resource-limited settings where neuroimaging is not immediately available, this bedside clinical tool can facilitate early risk stratification and timely referral for definitive diagnostic workup and stroke-specific care. Conclusion: The TriAge+ score, as an early clinical diagnostic tool in the ED, is essential for detecting central vertigo in order to reduce morbidity and mortality associated with cerebellar stroke.